2016
DOI: 10.1080/18756891.2016.1204124
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid gene expression programming algorithm based on orthogonal design

Abstract: The last decade has witnessed a great interest on the application of evolutionary algorithms, such as genetic algorithm (GA), particle swarm optimization (PSO) and gene expression programming (GEP), for optimization problems. This paper presents a hybrid algorithm by combining the GEP algorithm and the orthogonal design method. A multiple-parent crossover operator is introduced for the chromosome reproduction using the orthogonal design method. In addition, an evolutionary stable strategy is also employed to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 31 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…The experimental results showed that the proposed algorithm improved performances over several state-of-the-art algorithms in terms of accuracy and search efficiency. Yang and Ma [21] introduced an orthogonal design method into gene expression programming and proposed a new hybrid GEP algorithm. The comparative results demonstrated that the proposed algorithm had a better generalization ability than other traditional algorithms.…”
Section: B Gene Expression Programmingmentioning
confidence: 99%
“…The experimental results showed that the proposed algorithm improved performances over several state-of-the-art algorithms in terms of accuracy and search efficiency. Yang and Ma [21] introduced an orthogonal design method into gene expression programming and proposed a new hybrid GEP algorithm. The comparative results demonstrated that the proposed algorithm had a better generalization ability than other traditional algorithms.…”
Section: B Gene Expression Programmingmentioning
confidence: 99%
“…Zhang et al [6] and Zuo et al [7] combined GEP with differential evolution and found that their proposed algorithm performed better than the original GEP. Yang and Ma [8] used an orthogonal design for a multiple-parent crossover operator in chromosome reproduction. The study also introduced an evolutionary stable strategy to maintain population diver-sity during evolution.…”
Section: Introductionmentioning
confidence: 99%